Critiques and Appreciation on Orientalism in the Study of Islam - Fattah, Abdul (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
This article describes critiques on orientalism as well as appreciates orientalist works which have positive values in Islamic studies that requires “reassessment”. This is because orientalism is a distinctive discipline that has a strong historical value between the West and the East (Islam) after the medieval European renaissance. This discipline was initially used as a Western political tool to exploit the East—both aggression and imperialism. However this discipline deserves careful attention by removing prejudices-geopolitical and historical revenge in the orientalists’ objective judgments. The work produced by such orientalists cannot be solely underestimated. Some orientalists merely using a scientific or semi-scientific approach have continuously produced “magnum opus” and contributed to the development of Islamic studies such as Hadith index, Quranic dictionary, and Encyclopedia of Islam.